Water Physical Quality in the Mangrove Area of ​​the Air Telang Protected Forest During the West Season (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
This study investigates the water quality in the mangrove area of the Air Telang Protected Forest, Banyuasin Regency, during the western monsoon season. The research was conducted from February to October 2025 using a survey method. Sampling was carried out through purposive sampling at five observation stations: Station 1 (Pasir Timbul), Station 2 (Sonneratia zone), Station 3 (Avicennia zone), Station 4 (Nipah zone), and Station 5 (Rhizophora zone). The observed parameters included physical parameters (clarity, color, odor, and temperature). The results showed that among the physical parameters, only odor and temperature met the standards, whereas color and clarity did not. These findings indicate that the water quality in the Air Telang Protected Forest during the western monsoon season is potentially polluted.